Residência multiprofissional em cancerologia: expressões da integralidade do cuidado - Leitão, Bruna Fabrícia Barboza (2018)
The Multi-professional Residency Program in Health emerges as an important axis of action of the National Policy of Permanent Education in Health, as it aims to improve health work practices, by problematizing the daily problems of workers, valuing their own experiences and self-work as a raw material for learning processes. The health services network is legitimated as potential learning scenarios, aiming at strengthening workers as autonomous and creative subjects facing reality. The Multi-professional Residency Program in Cancerology, in turn, is justified by the importance of training programs that aim to qualify care and promote the permanent education of professionals in this area, seeing that cancer is recognized as a significant public health problem in Brazil, considering its social magnitude expressed by the progressive coefficients of morbidity and mortality. Regarding integrality in health, in addition to conceptualization as a principle of the Unified Health System [Brazil's Public Health System] and despite the inherent polysemy of the term, the notion of wholeness was highlighted as a know-how that is essentially ethical and, therefore, culminates in care with the other, as a political posture capable of reorienting hegemonic practices in health, provided with ethical and necessarily collective values. Based on these references, this research aimed to understand, from the perspective of the retired residents, how the integrality of care is expressed in the training process of the Integrated Residency in Health with an emphasis on Cancerology of the School of Public Health of Ceará and the Cancer Institute of Ceará. Methods: This was a qualitative study carried out with the participation of 30 residents of 06 different professional categories from the Integrated Residency Program in Health with emphasis on Cancerology. For the construction of the empirical data, focal groups were defined as the main technique, made possible through collective interviews guided by a previously established script. The analysis of the data was guided by the reference of the Critical Hermeneutics of Gadamer, from which it was sought the understanding of the original senses of the object of study in question. Analysis and discussion of the results: Based on a comprehensive analysis of the data constructed in the empirical field, the results were organized in an interpretative network constituted by three dimensions: Interprofessionality, Integrality and Interfaces between Multi-professional Residences Programs in Health and Integrality. The analyzes revealed that the main meanings of integrality recognized by the residents appear to be associated with the dimension of interprofessionality and the perspective of network attention, although these are crossed by several obstacles and challenges specific to the hospital scenario. Among the theoretical activities, it was noticed that the strategies pointed out in the pedagogical design used by Integrated Residency in Health with an emphasis on Cancerology, allow the construction of dialogic and reflexive spaces about integrality and interprofessionality. Regarding the practical component, it is highlighted as greater potentiality and challenge the exercise of work in interprofessional teams. The Multi-professional Residency Program in Health, inasmuch as it proposes to work in the perspective of Permanent Education in Health, encourages in the residents the practice of in-service learning essentially problematizing the knowledge and practices instituted, aspect that, although powerful in terms of learning, can be the source of many everyday conflicts. Final considerations: The Integrated Residency in Health with an emphasis on Cancerology stands out as a potent health education strategy, combining in its processes the technical and political dimensions, making it possible to go beyond the specialisms that imprison professionals in the restricted areas of corporate power and, therefore, impedes the exchange between the diversity of voices present in the field of health, a condition considered indispensable for the guarantee of the integrality of attention.